Anapole-excited terahertz multifunctional spoof surface plasmon polariton directional Janus metastructures - Pan, Hao; Li, Bing-xiang; Zhang, Hai Feng (Physical chemistry chemical physics : PCCP, 2023)
The anapole mode, in which a distinct radiationless electromagnetic (EM) response in artificial media can be achieved, has attracted significant attention and been regarded as a promising candidate to initiate novel avenues to control the intrinsic radiative losses in nanophotonics and plasmonics, whose current research studies mainly focus on the manipulation of the one-directional incident wave. To exploit the propagation characteristic of incident waves in anapole-excited (AE) media, a set of terahertz (THz) multifunctional Janus metastructures (JMSs) for the opposite linear-polarized (LP) light excitation is presented in this paper. By introducing the directional-selective spoof surface plasmon polariton (SSPP) excited by anapole mode, a metastructure rasorber (MSR) possessing an absorption band of 2-3.08 THz (42.5%) and a co-polarized transmission window of 3.77-5.55 THz (38.2%) for the forward normal-incident LP wave is attained. Furthermore, the integration of the MSR and a polarization-conversation structure (PCS) can be used to fabricate a multifunctional Janus metadevice thus achieving the integration of EM energy harvesting, the co-polarized transmission, and cross-polarized reflection of light with opposite propagation directions, i.e. , an absorption band of 2.14-3.09 THz (36.3%) for the forward normal-incident LP wave, and a cross-polarized reflection band of 2.08-3.03 THz (37.2%) for the backward vertical-incident LP wave, while attaining an identical co-polarized transmission window of 3.95-5.2 THz (27.3%). Moreover, by utilizing the substantial field-localization properties of anapole modes supported by the nested opposite-directional SSPP with different sizes, the Janus metastructure absorber (JMA) can achieve non-overlapped absorption bands of 2.02-2.84 THz (33.7%) and 2.88-4.58 THz (45.6%) for the bidirectional normal-incident LP waves, respectively. A series of passive JMSs based on the anapole modes excited by the opposite-directional incident waves significantly extend the theoretical framework and application field of multipole electrodynamics, especially aimed at directional-selective management. A unidirectional MSR based on gradient AE SSPP can realize a Janus metadevice which is an absorber or a polarization rotator.